The Effect of Teaching Reading Methods and Learning Motivationon the stdent’s Achievement in Reading Comprehension - Sa'adah Bahri Rangkuti; Berlin Sibarani; D.P. Tampubolon (LINGUISTIK TERAPAN, 2014)
The objectives of this study were to investigate whether: (1) Students’ achievement in reading comprehension taught by using SPE is higher than students’ Achievement in Reading comprehension taught by using SQ4R, (2) Reading comprehension achievement of high learning motivation students is higher than reading achievement of low learning motivation students, and (3) There is significant interaction between teaching reading methods and students learning motivation on students reading comprehension achievement. An experimental research with factorial design 2x2 was used in this research. The first group was treated by using SPE and the second group was treated by using SQ4R. The learning motivation test was conducted for classifying the students upon the high learning motivation and the low learning motivation. The data were analyzed by applying Two-Way ANOVA. The result reveals that (1) students achievement in reading comprehension taught by using SQ4R is higher than that of taught by using SPE, (2) reading comprehension achievement of high learning motivation students is higher that reading achievement of low learning motivation students (3) There is significant interaction between teaching reading method and students learning motivation on students achievement in reading comprehension. Thus, teaching methods and students’ learning motivation significantly affect the students’ achievement in reading comprehension. Keywords: Motivation; Reading Comprehension; and Teaching Reading Methods.